2017
DOI: 10.3892/ol.2017.6588
|View full text |Cite
|
Sign up to set email alerts
|

Difference in expression of two neurokinin-1 receptors in adenoma and carcinoma from patients that underwent radical surgery for colorectal carcinoma

Abstract: Abstract. Mechanisms underlying tumor progression remain a main problem in the diagnosis and treatment of patients with tumors. The present study compared the expression of full-length neurokinin-1 receptors (fl-NK-1R) and truncated neurokinin-1 receptors (tr-NK-1R) in adenoma and carcinoma from patients with colorectal carcinoma, to explore their possible contributions in adenoma-carcinoma progression. Samples were collected immediately following colorectal carcinoma surgery. Using reverse transcription-quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Consistently, Pagan et al (61) showed that the administration of SR140333 (1 mg/kg), an NK1R antagonist, dose-dependently exerts proapoptotic functions via inducing the suppression of extracellular signal-regulated kinases 1 and 2 (ERK1/2) and cyclooxygenase 2 (COX-2) signaling cascades in a rat model of CRC. To further support the regulatory role of TKs in CRC progression and development, Gao et al (62) indicated that interaction of truncated-NK1R (tr-NK1R), as a dominant form of NK1R, with its ligand probably play an essential role in the tumor microenvironment. In addition, these findings suggested that diminishing the expression of tr-NK1R may be used as a potential therapeutic strategy to prevent dysplasia of the colorectal adenomas from progressing to colorectal carcinomas (62).…”
Section: Tks and Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, Pagan et al (61) showed that the administration of SR140333 (1 mg/kg), an NK1R antagonist, dose-dependently exerts proapoptotic functions via inducing the suppression of extracellular signal-regulated kinases 1 and 2 (ERK1/2) and cyclooxygenase 2 (COX-2) signaling cascades in a rat model of CRC. To further support the regulatory role of TKs in CRC progression and development, Gao et al (62) indicated that interaction of truncated-NK1R (tr-NK1R), as a dominant form of NK1R, with its ligand probably play an essential role in the tumor microenvironment. In addition, these findings suggested that diminishing the expression of tr-NK1R may be used as a potential therapeutic strategy to prevent dysplasia of the colorectal adenomas from progressing to colorectal carcinomas (62).…”
Section: Tks and Colorectal Cancermentioning
confidence: 99%
“…To further support the regulatory role of TKs in CRC progression and development, Gao et al (62) indicated that interaction of truncated-NK1R (tr-NK1R), as a dominant form of NK1R, with its ligand probably play an essential role in the tumor microenvironment. In addition, these findings suggested that diminishing the expression of tr-NK1R may be used as a potential therapeutic strategy to prevent dysplasia of the colorectal adenomas from progressing to colorectal carcinomas (62). Besides, another in vitro study presented evidence that NKP608, as a selective and specific NK1R antagonist, leads to induced inhibiting the cell growth, invasion, migration, as well as enhanced programmed cell death in the human CRC cells, via suppressing the Wnt/β-catenin signaling axis (63).…”
Section: Tks and Colorectal Cancermentioning
confidence: 99%